"The Way You Enter a Church": The Dialectics of Ken Burns's Baseball. (December 2020) - Jenemann, David
Taken as a whole, Ken Burns's 1994 documentary Baseball and its 2010 follow-up The Tenth Inning stand as some of the most influential documentaries on the history of American sports. Baseball develops the link between the "fun" of the game and philosophical beliefs about American democracy through a "dialectical aesthetic" that operates through Baseball's choice of subjects and historical events as well as through its formal documentary strategies. While many critics dismiss Baseball as overly nostalgic, this essay argues that Baseball engages the reader with the dialectic to encourage self-reflection about the future of the game and its role in civil society.